Sliding-impact bistable triboelectric nanogenerator for enhancing energy harvesting from low-frequency intrawell oscillation. (1st February 2023) - Tan, Dongguo; Zhou, Jiaxi; Wang, Kai; Ouyang, Huajiang; Zhao, Huai; Xu, Daolin
Highlights: A new bistable TENG coupling the sliding and impact modes (SIBTENG) is proposed. Impact mode is employed to enhance energy harvesting efficiency during intrawell oscillation. The output power is improved by 100% by impact mode when undergoing intrawell oscillation. The SIBTENG enables high-efficiency energy harvesting whatever the oscillation pattern is. Abstract: A sliding-mode bistable triboelectric nanogenerator (SBTENG) has already been proven to be highly efficient for harvesting energy from low-frequency vibration. However, a SBTENG would undergo low-amplitude intrawell oscillation and thus output low power, if the excitation is weak. To enhance the efficiency of harvesting energy from low-frequency intrawell oscillation, a novel sliding-impact bistable TENG (SIBTENG) is proposed. The sliding-mode component of the SIBTENG enables energy harvesting from interwell oscillation effectively, while the impact-mode structure plays a vital role in enhancing energy harvesting from intrawell oscillation. The equation of motion of the SIBTENG is derived using Hamilton's principle and then numerically solved to obtain the dynamic responses. Subsequently, the output performance of the SIBTENG is evaluated by solving the electrical equation, which is unidirectional coupled to the equation of motion. Finally, experiments on the prototype of the SIBTENG are conducted to verify this design concept, which indicates good consistency between the theoretical and experimental results. Importantly, the impact-mode structure can notably enhance energy harvesting from intrawell oscillation. The output power of the devised SIBTENG is improved by about 100% over the SBTENG when they experience intrawell oscillation. The SIBTENG thereby enables high-efficiency energy harvesting whatever the oscillation pattern is.